Physico-chemical analysis of fillets of the exotic species Hemiancistrus aspidolepis in Costa Rica - Peña-Navarro, Nelson (2021)
Introduction. When invasive animal species are introduced into an ecosystem that is not their natural range, their control could be determined by the possibility of using these organisms for human consumption or other management alternatives. Objective. To determine the physical-chemical characteristics of the H. aspidolepis fillet, and to compare its nutritional quality with fish species for human consumption of marine origin and continental waters. Materials and methods. 109 fish were collected in three Wildlife Refuges in Costa Rica, during 2017, they were weighed fresh and without viscera, in addition each fillet, viscera, and carcass were weighed. A proximal analysis was performed to determine the content of fatty acids, minerals, and mercury. Results. The average length of the collected individuals was 25.35 cm and the average weight was 162.55 g, of which 8.2 % were viscera, and 19.02 % were muscle. For each sample, there were obtained averages per 100 g of: 80.69 g of water, 17.64 g of protein and 73.40 kcal of energy. The levels of trans fat and total carbohydrates were 0.01 and 0.55 g 100 g-1, respectively. The minerals per 100 g were 281.81 mg of potassium, 28.87 mg of sodium, and 1.23 mg of iron. The fatty acids in greater quantity were: palmitic (23.64 %), stearic (9.43 %), and tricosanoic (7.26 %). The total mercury level was less than 0.15 ppm. Conclusions. The collected individuals did not have similar sizes and weight percentages of fillets to those used for market and human consumption. H. aspidolepis has similarities in proximal content, fatty acids, and minerals with respect to some fish for human consumption; the contents of proteins and lipids make it suitable for consumption and commercialization.